2002
DOI: 10.2460/javma.2002.220.342
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study of fecal shedding of Clostridium perfringens in broodmares and foals

Abstract: Clostridium perfringens was identified from the feces of all but 6 foals by 3 days of age and is likely part of the normal microflora of neonatal foals. Most isolates from broodmares and foals are C. perfringens type A; thus, the clinical relevance of culture results alone is questionable. Clostridium perfringens type C, which has been associated with neonatal enterocolitis, is rarely found in the feces of horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 13 publications
4
54
2
2
Order By: Relevance
“…The prevalence of 57% for fecal shedding of C. perfringens is similar to a previous study where a prevalence of 62% in 0‐ to 2‐month‐old foals was reported 21. Unlike with C. difficile , the prevalence did not decrease substantially at 6 weeks of age, which is consistent with a previous study where prevalence rates remained at 30% at 1–2 months of age 21…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of 57% for fecal shedding of C. perfringens is similar to a previous study where a prevalence of 62% in 0‐ to 2‐month‐old foals was reported 21. Unlike with C. difficile , the prevalence did not decrease substantially at 6 weeks of age, which is consistent with a previous study where prevalence rates remained at 30% at 1–2 months of age 21…”
Section: Discussionsupporting
confidence: 90%
“…The role of enterotoxin as a virulence factor in equine gastrointestinal disease remains controversial. Although accounting for only 10% of isolates from foals, enterotoxigenic strains were significantly associated with diarrhoea in one report (Netherwood et al 1998b) and enterotoxin was detected in 28% of foals with diarrhoea, while the toxin or isolates carrying its gene were identified in 0-2% of normal foals (Tillotson et al 2002, Weese et al 2001). Nevertheless, due to its infrequent presence it has been suggested that the toxin alone can not account for the overall association of C. perfringes with diarrhoea in foals (Netherwood et al 1998b).…”
Section: Rotavirusmentioning
confidence: 99%
“…The prevalence decreases with age, but the organism can still be found in 30-35% of brood mares and foals 1-2 months of age (Tillotson et al 2002). The organism is categorized into types A-E based on the expression of one or a combination of major lethal exotoxins.…”
Section: Rotavirusmentioning
confidence: 99%
See 2 more Smart Citations